Urgensi Mind dalam Interaksi Simbolik Komunikasi Antar Pribadi Dosen dan Mahasiswa - Ramadhani, Salilah Zahira; Tazkia, Hana Rizqy; Salwa, Putri Giani Nabila; Sari, Yunita (Jurnal Pustaka Komunikasi, 2025)
George Herbert's symbolic interaksionisme theory of Herbert Mead confirmed that human communication occurred through symbols that have a social meaning. In this perspective, mind (mind) plays a crucial role as the capacity to interpret symbols, provide reflective response, and executes the interaction. In a lecturer relationship - students, the implementation of the mind frame is the basis to reduce the risk of miscommunication and improve the quality of interpersonal relationships through empathic attitudes and openness. This research adopted a qualitative descriptive approach with a phenomenology foundation to explore the subjective experience of communication actors. Informants consist of two senior lecturers who have a teaching experience of more than ten years and two S2 program students who often interact formally or informally at a private university in Jakarta. The findings show that the urgency of the mind is seen in the symbol exchange process between lecturers and students; mind serves as an internal mechanism that includes perception, understanding, attitudes/emotions, motivation, and awareness of roles. Thus, mind plays an important role in the formation of meaning, smooth interpersonal communication, and strengthening academic relationships.